Kebijakan Reorganisasi Perizinan untuk Meningkatkan Kualitas Pelayanan Publik di Kota Yogyakarta - Isnaini Muallidin (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2011)
The purpose of this research was to evaluate the reorganization of the licensing policy to improve the quality of public services in the City Yoyakarta. The method used in this study was to evaluate the research methods of interviews, observation, and secondary data from relevant sources. The results showed that the reorganization UPTSA into Dinas Perizinan has provided many benefits to society, because a permit can be done one door with an integrated system. So that a permits be efficient and effective because of the simplification of systems and procedures for information technology-based services. The conclusion of this study was the reorganization of licensing policy has provided a paradigm shift in the public service-oriented accountability system that has been adjusted to the needs of the community.